Brand Identity Management and Corporate Social Responsibility: an analysis from employees' perspective in the banking sector. Issue 2 (4th March 2017) - Bravo, Rafael; Buil, Isabel; de Chernatony, Leslie; Martínez, Eva
Abstract: Brand identity management and corporate social responsibility have increased importance in both managerial practice and academic research. However, only a small number of studies have examined how these strategic tools influence employees' attitudes and behaviours. The aim of this paper is, therefore, to analyse how employees' perceptions of brand identity management and corporate social responsibility affect their attitudes and behaviours. An empirical study was undertaken among a sample of 297 front line employees working in the UK banking sector. Hypotheses were tested using partial least square regression. The results show that employees' perceptions of brand identity management and corporate social responsibility determine their commitment towards their organisations, both directly and indirectly through perceived external prestige. Organisational commitment explains employees' brand performance and brand citizenship behaviour. Age differences indicate higher impact of brand identity management on older employees, and higher effects of perceived corporate social responsibility in younger employees. The results extend existing knowledge and are informative for bank managers.